Factors related to export intensity of Filipino agripreneurs - De Castro, Melodee Marciana (Journal of Economics, Management & Agricultural Development, 2018)
This paper aims to determine the factors related to the intensity of Filipino agripreneurs. Secondary data from the Global Entrepreneurship Monitor (GEM) Philippine economy database were utilized.